Jamaican immigrants in the United States and Canada : race, transnationalism, and social capital - Jones, Terry-Ann, 1977- (New Americans (LFB Scholarly Publishing LLC), 2008)
"Terry-Ann Jones is Assistant Professor in the Department of Sociology and Anthropology at Fairfield University."--Jacket.